Obstetrics: Contribution of the Peruvian Society of Obstetrics and Gynecology in 70 years of institutional life - Guevara Rios, Enrique (2017)
The Peruvian Society of Obstetrics and Gynecology has had and will continue to contribute to the development of obstetrics in Peru, through its academic activities and scientific articles published in The Peruvian Journal of Gynecology and Obstetrics. In the field of Obstetrics, the journal has covered several topics related to maternal mortality, diagnosis and management of obstetric hemorrhage, preeclampsia, infections in obstetrics, abortion and the evolution of cesarean technique have been written.